Sleep quality as a predictor of sexual dysfunction in men with type 2 diabetes - Srinivas, Miriyala S.; Shivam; Jain, Tarak; Prahaladbhai, Patel A.; Devraj, Srilakshmi; Mohanty, Lalatendu; Das, Sambit (International Journal of Research in Medical Sciences, 2025)
Background: Sexual dysfunction and hypogonadism are common yet under‐recognized complications of type 2 diabetes mellitus (T2DM). Sleep disturbances—particularly clinical insomnia—may exacerbate neuroendocrine and metabolic dysregulation, but their role as predictors of sexual dysfunction and testosterone deficiency in diabetic men remains unclear. Methods: In this cross‐sectional study, 54 men with T2DM (age 35–60 years) attending our outpatient clinic were evaluated for insomnia (insomnia severity index, ISI), hypogonadal symptoms (androgen deficiency in ageing male, ADAM questionnaire), morning serum total testosterone (TT), and sexual dysfunction (self‐reported clinical interview). Clinical insomnia was defined as ISI >15; biochemical hypogonadism as TT <3 ng/ml; confirmed hypogonadism as ADAM‐positive plus TT <3 ng/ml. Participants were stratified by insomnia status (n=18 versus 36) and compared using t–tests and χ² tests. Logistic regression adjusted for age, body mass index (BMI), glycated haemoglobin (HbA1c), and diabetes duration identified independent predictors of confirmed hypogonadism. Results: Clinical insomnia was present in 33.3% of the cohort. Overall, 37.0% of men reported sexual dysfunction. Insomniac participants had higher rates of sexual dysfunction (66.7% versus 22.2%; p<0.001), ADAM‐positivity (83.3% versus 36.1%; p=0.001), biochemical hypogonadism (44.4% versus 11.1%; p=0.006), and confirmed hypogonadism (38.9% versus 8.3%; p=0.014) compared to non‐insomniacs. In multivariable analysis, clinical insomnia remained the only independent predictor of confirmed hypogonadism (OR 12.14; 95% CI 1.16–126.60; p=0.037). Conclusions: Clinical insomnia in men with T2DM is strongly associated with both sexual dysfunction and testosterone deficiency, and independently predicts confirmed hypogonadism. These findings support integrating sleep‐quality assessment into diabetic care pathways and targeting insomnia as a modifiable factor to improve sexual and endocrine health.